Continuous manipulation of acoustic wavefront using a programmable acoustic metasurface. (18th May 2021) - Gong, Kemeng; Zhou, Xin; Ouyang, Huajiang; Mo, Jiliang
Abstract: Conventional passive acoustic metasurfaces (AMSs) can hardly reconfigure their topologies or structural parameters, which limits their wide applications. In this paper, a programmable AMS which contains an array of reconfigurable subwavelength unit cells, regulated by a set of stepper motors with lead screws and a cost-effective control system is presented. The unit of the AMS is composed of a parallel one-dimensional daisy-chained slit with five Helmholtz resonators. The phase shift of the transmission wave through the AMS units can be precisely controlled over the full phase range and continuously tuned by varying the slit width at high transmission efficiency. Benefitting from such a mechanism, the designed AMS is able to achieve continuous versatile wave manipulation functions in simulation and in experiment by engineering the phase and amplitude of transmission waves, including tuneable acoustic refraction, tuneable acoustic focusing and tuneable acoustic self-bending. Thus, this proposed AMS holds a great potential for a wide range of applications including diagnostic sonography, active non-destructive evaluation, acoustic holography, noncontact micro-particles manipulation and energy harvesting.